The art of the start 2.0 : the time-tested, battle-hardened guide for anyone starting anything - Kawasaki, Guy, 1954- (New York : Portfolio/Penguin, 2015)
Newly revised and updated, a 10th-anniversary edition of an iconic, best-selling guide for start-ups provides expert advice on a wealth of topics -- including writing a business plan, recruiting, raising capital and branding. --Publisher's description.
Conception : The art of starting up -- Activation : The art of launching -- The art of leading -- The art of bootstrapping -- The art of fund-raising -- The art of pitching -- Proliferation : The art of building a team -- The art of evangelizing -- The art of socializing -- The art of rainmaking -- The art of partnering -- The art of enduring -- Obliation : The art of being a mensch -- Afterword -- What do entrpreneurs do? -- After afterword.
Includes bibliographical references and index.
Keywords: New business enterprises; Entrepreneurship